Epidemiological characteristics and antimicrobial susceptibility among carbapenem-resistant non-fermenting bacteria in Brazil - Vanessa Cordeiro Dias; Claudio Galuppo Diniz; Ana Claudia de Oliveira Peter; Andre Netto Bastos; Victor Quinnet de Andrade Bastos; Lucas Quinnet de Andrade Bastos; Vania Lucia da Silva (Journal of Infection in Developing Countries)
Introduction: Non-fermenting Gram-negative bacteria such as Pseudomonas aeruginosa and Acinetobacter baumannii are widespread in the environment and are increasingly associated with nosocomial infections. Extensive and indiscriminate use of antibiotics in hospitals has contributed to an increased number of infections caused by these microorganisms, that are resistant to a wide variety of antimicrobials, including β-lactams. This study aimed to isolate and identify carbapenem-resistant Acinetobacter spp. and P. aeruginosa from hospitalized patients, to determine their antimicrobial susceptibility patterns and to screen for blaOXA-23, blaOXA-24, blaOXA-51, blaOXA-58, and blaOXA-143 genes among the isolated bacteria. Methodology: Antimicrobial resistance patterns were performed using the disk-diffusion method. Genetic markers related to carbapenem resistance were screened by polymerase chain reaction. Results: Carbapenem-resistant Acinetobacter spp. (n = 44) and P. aeruginosa (n = 28) samples were isolated from patients admitted to a tertiary hospital. Polymyxin B was the only effective drug for all isolates. Considering the oxacillinase gene screening, genetic markers were observed only in Acinetobacter isolates. The most frequent genotype observed was blaOXA-23+/blaOXA-51+ (45.5%), followed by blaOXA-51+/blaOXA-143+ (41%). The oxacillinase genes blaOXA-24 and blaOXA-58 were not detected. High mortality rates (> 70%) were observed. Conclusions: The data suggest the need for rational use of antimicrobials associated with early diagnosis of multidrug-resistant bacteria, especially considering non-fermenting Gram-negative rods, which are widespread in hospitals. The findings of blaoxa-51‑ strains suggest the occurrence and spread of non-A. baumannii species throughout our hospitals. Effective implementation of surveillance programs in hospitals is needed to reduce infectious and resistant intra- and inter-species bacteria.